Patients' experiences of unilateral spatial neglect between stroke onset and discharge from inpatient rehabilitation: a thematic analysis of qualitative interviews. Issue 11 (21st May 2020) - Tobler-Ammann, Bernadette C.; Weise, Andrea; Knols, Ruud H.; Watson, Martin J.; Sieben, Judith M.; de Bie, Rob A.; de Bruin, Eling D.
Abstract: Purpose: The purpose of this qualitative study was to explore how stroke patients with unilateral spatial neglect experience; (a) performance in activities of daily living; (b) alterations in bodily perceptions; and (c) personal hopes and expectations, looking at the period between stroke onset and discharge from inpatient rehabilitation. Materials and methods: We conducted individual semi-structured interviews with 7 (5 men, 2 women, mean age 69 years) consecutively sampled participants. All interviews were transcribed verbatim and analyzed using thematic analysis. Findings: Participants' experiences were captured in three over-arching themes: "unawareness of neglect, " "emergent awareness for neglect-related difficulties, " and "comparing the new life with the old one . " Findings showed that participants progressed from initial unawareness to emergent awareness for their neglect-related difficulties over the course of rehabilitation. Comparing their current life situation with the one before their stroke triggered feelings of uncertainty and regret, with associated decreased pleasure in meaningful activities. Conclusions: This study informs health professionals regarding personal experiences of orientation in and reorganization of life of stroke patients with unilateral spatial neglect. The findings highlight that being aware of neglect-related deficits is a prerequisite for using coping strategies and incorporating them in daily life. Possible therapeutic strategies that fit the current stage of recovery and level of awareness are discussed. IMPLICATIONS FOR REHABILITATION: Symptoms of unilateral spatial neglect and anosognosia are most common after right hemispheric stroke, both being predictors of poorer functional outcome during rehabilitation. Patients' regaining some awareness of their impairments is a prerequisite for successful treatment and for engagement in neglect-specific interventions. Health care providers should carefully examine the "state of awareness" of the patient and adapt their therapeutic approach accordingly. This check should frequently be repeated over the course of rehabilitation, as awareness changes at different paces for each patient.